From Familiar Faces to Family: Staff and Resident Relationships in Long-Term Care. (August 2017) - Canham, Sarah L.; Battersby, Lupin; Fang, Mei Lan; Sixsmith, Judith; Woolrych, Ryan; Sixsmith, Andrew
Objective: Long-term care (LTC) facilities are increasingly intent on creating a "homelike" atmosphere for residents. Although residential staff are integral to the construction of a home within LTC settings, their perceptions have been relatively absent from the literature.Method: Thirty-two LTC staff participants were interviewed about their experiences and perceptions of the physical environment and conceptualizations of home, and thematic analyses were conducted.Results: An overarching category—interpersonal relationships—emerged from our analyses emphasizing the importance of relationships in creating a homelike environment within institutional settings. Sub-themes that inform our understanding include the following: (a) Staff members' perceptions of home; (b) "Their second home": Adjustment to and familiarity in LTC; and (c) "We become family": Relationality makes a home.Discussion: The study provides evidence to inform current policies and practices in LTC. Specifically, enough time and space should be given to residents and staff to create and maintain personal relationships to make residential care homelike.